The Impact of Dashboard Characteristics on the Utilization and Usefulness of Dashboards in Moroccan Companies - RHERIB, Nada (International Journal of Scientific Research and Management (IJSRM), 2024)
The objective of this research is to determine the impact of dashboard characteristics on the use and usefulness of dashboards of Moroccan companies. In this paper, we will first present the theoretical foundations of our research. Then, following a hypothetico-deductive approach and a positivist positioning, an explanatory model of our two variables was proposed; “Characteristics of dashboards” and “Uses and usefulness of dashboards”. In this perspective, we adopted a quantitative methodology based on a questionnaire administered online to management controllers of Moroccan companies. And finally, we tested our model with 117 Moroccan companies. The collected data is analyzed by structural equation methods (PLS) on SMARTPLS. The results of this research work made it possible to validate the hypotheses which stipulate that there is an impact of the characteristics of the dashboards on the use and usefulness of the dashboards of Moroccan companies. This work enriches previous work on dashboards